Про середньоквадратичне обернення однiєї диференцiальної моделi нелiнiйного просторово-часового процесу з дискретно визначеними збурюючими факторами - Стоян, В.В. (Видавничий дім "Академперіодика" НАН України, 2008)
A dynamic process, whose function of state is a product of its linear transformations, is examined. An integral representation of the rootmean-square inversion approximation of such a function is built for the case of discretely defined perturbing factors. Exactness of the approximation obtained is estimated.